A temporal reasoning framework used in the diagnosis of skeletal dysplasias - Washbrook, John; Keravnou-Papailiou, Elpida (My University, 1990)
The representation of and reasoning with temporal information in the diagnosis of skeletal dysplasias and syndromes is discussed. Temporal reasoning is relevant to most medical problems and the framework presented has been developed with a view to applications in other domains, both medical and non-medical
Keywords: Artificial intelligence; Computer science; Medicine; Diagnosis; Expert systems (Computer science)